Implementasi Metode Ritme Otak (MRO): Studi Capaian Siswa dalam Pembelajaran Hafalan Al-Qur'an di Madrasah Aliyah Sunanul Husna Ciputat Tangerang Selatan - Rusjdy Sjakyakirti Arifin; Busahdiar; Saviratu Syahdiani (UIN Sunan Gunung Djati Bandung, 2022)
There are many obstacles faced by students in memorizing the Qur'an. One of them is that the appropriate memorization method has not been used, so the ability to memorize the Qur'an has not been achieved. There are many choices of methods that can be used by educators so that students can memorize the Qur'an as expected. The Brain Rhythm Method is one of them. This study aims to investigate the effect of the Brain Rhythm Method on the ability to memorize the Qur'an in students at Madarasah Aliyah Sunanul Husna Ciputat, South Tangerang. This research approach uses quantitative research using experimental methods. The research design used quasi-experimental. The population of this study was all students of Madrasah Aliyah Sunanul Husna, totaling 244 students. The population was reached by 61 people from all 12th-grade students consisting of 3 study groups. 40 students from two study groups, namely class 12 a and class 12b were sampled in this study. Questionnaires were used for data collection. Data analysis used the technique of an Independent simple t-test. The results showed that T-count = 6.698 > P-value 0.000, meaning that H0 was rejected. So the Brain Rhythm Method has an effect on the ability to memorize the Qur'an of students at Madrasah Aliyah Sunanul Husna Ciputat South Tangerang.